2015
DOI: 10.1590/0004-282x20140235
|View full text |Cite
|
Sign up to set email alerts
|

In adolescents with epilepsy, high scores of anxiety and depression are associated with occurrence of seizures in public places

Abstract: Objective: To assess depression and anxiety symptoms of adolescents with epilepsy compared with adolescents without epilepsy. Method: The study sample consisted of: case participants (50 subjects) attending the pediatric epilepsy clinic of a tertiary hospital and control participants (51 subjects) from public schools. The instruments utilized were: identification card with demographic and epilepsy data, Beck Depression Inventory and State-Trait Anxiety Inventory. Results: No significant differences were founde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…Ettinger et al and Baki et al did not find any significant correlation between number of seizures and anxiety and depression scores (11)(12)(13). However, most studies have suggested that affective disturbances are associated with seizure frequency (10,(14)(15)(16). The present findings demonstrate that there is no correlation between affective disturbances and seizure frequency.…”
Section: Discussioncontrasting
confidence: 48%
“…Ettinger et al and Baki et al did not find any significant correlation between number of seizures and anxiety and depression scores (11)(12)(13). However, most studies have suggested that affective disturbances are associated with seizure frequency (10,(14)(15)(16). The present findings demonstrate that there is no correlation between affective disturbances and seizure frequency.…”
Section: Discussioncontrasting
confidence: 48%
“…This finding supported reports from other studies. 13,21,22 On the other hand, moderate to severe depression was more common in a study by Pereira and Valente. 23 The difference observed could be due to the study populations.…”
Section: Discussionmentioning
confidence: 92%
“…According to a study by the Department of Neurology at the State University of Campinas (Unicamp), there is no higher incidence of depression or anxiety in the group of teenagers with epilepsy compared to the control group by seeing the diagnostic scores of both [14]. But it was observed that there is a lower frequency of seizures when there are low scores of trait or states of anxiety.…”
Section: Discussionmentioning
confidence: 99%